Single-cell Sequencing of Thiomargarita Reveals Genomic Flexibility for Adaptation to Dynamic Redox Conditions - Winkel, Matthias; Salman-Carvalho, Verena; Woyke, Tanja; Richter, Michael; Schulz-Vogt, Heide N.; Flood, Beverly E.; Bailey, Jake V.; Mußmann, Marc (Frontiers in Microbiology, 2016)
Large, colorless sulfur-oxidizing bacteria (LSB) of the family Beggiatoaceae form thick mats at sulfidic sediment surfaces, where they efficiently detoxify sulfide before it enters the water column. The genus Thiomargarita harbors the largest known free-living bacteria with cell sizes of up to 750 μm in diameter. In addition to their ability to oxidize reduced sulfur compounds, some Thiomargarita spp. are known to store large amounts of nitrate, phosphate and elemental sulfur internally. To date little is known about their energy yielding metabolic pathways, and how these pathways compare to other Beggiatoaceae. Here, we present a draft single-cell genome of a chain-forming "Candidatus Thiomargarita nelsonii Thio36", and conduct a comparative analysis to five draft and one full genome of other members of the Beggiatoaceae. "Ca. T. nelsonii Thio36" is able to respire nitrate to both ammonium and dinitrogen, which allows them to flexibly respond to environmental changes. Genes for sulfur oxidation and inorganic carbon fixation confirmed that "Ca. T. nelsonii Thio36" can function as a chemolithoautotroph. Carbon can be fixed via the Calvin-Benson-Bassham cycle, which is common among the Beggiatoaceae. In addition we found key genes of the reductive tricarboxylic acid cycle that point towards an alternative CO2 fixation pathway. Surprisingly, "Ca. T. nelsonii Thio36" also encodes key genes of the C2-cycle that convert 2-phosphoglycolate to 3-phosphoglycerate during photorespiration in higher plants and cyanobacteria. Moreover, we identified a novel trait of a flavin-based energy bifurcation pathway coupled to a Na+-translocating membrane complex (Rnf). The coupling of these pathways may be key to surviving long periods of anoxia. As other Beggiatoaceae "Ca. T. nelsonii Thio36" encodes many genes similar to those of (filamentous) cyanobacteria. In summary, the genome of "Ca. T. nelsonii Thio36" provides additional insight into the ecology of giant sulfur-oxidizing bacteria, and reveals unique genomic features for the Thiomargarita lineage within the Beggiatoaceae.